Experimental evaluation of cohesive and adhesive bond strength and fracture energy of bitumen-aggregate systems - Zhang, Jizhe; Airey, Gordon D.; Grenfell, James R.A. (Springer, 2016)
Degradation of asphalt pavements is an inevitable phenomenon due to the combined effects of high traffic loads and harsh environmental conditions. Deterioration can be in the form of cohesive failure of the bitumen and/or bitumen-filler mastic or by adhesive failure between bitumen and aggregate. This paper presents an experimental investigation to characterise the cohesive and adhesive strength and fracture energy of bitumen-aggregate samples. The pneumatic adhesion tensile testing instrument test and the peel test were used to quantify the tensile fracture strength and fracture energy of different bitumen-aggregate combinations, with a view to analyse the influence of several parameters on the strength of the bitumen film or bitumen-aggregate interface. From the experimental results, harder (40/60 pen) bitumen tends to show much higher tensile strength and fracture energy than softer (70/100 pen) bitumen. Tensile strength is shown to be sensitive to testing temperature with the failure regime changing from cohesive to mixed cohesive/adhesive failure with decreasing temperature. In addition, the results show that aggregate properties do not influence the bonding strength if cohesive failure occurs, but with adhesive failure, granite aggregate tends to produce a higher bonding strength than limestone aggregate in the dry condition. In terms of the peel test, the fracture energy experienced an increasing trend with increasing film thickness. However, the normalised toughness decreased when film thickness increased from 0.2 to 0.9 mm.